Organizational Resilience in the Face of Global Crises: Risk Management and Strategy Adaptation Perspectives - Kusmawan, Asep; Septiarini, Isna Nur; Lestari, Lestari (Maneggio, 2026)
The increasing frequency of global crises, including health emergencies, economic instability, climate change, and digital disruption, has intensified the need for organizational resilience that goes beyond survival toward sustainable transformation. This study aims to analyze how organizational resilience can be strengthened through the integration of risk management frameworks and strategic adaptation mechanisms. A qualitative approach using a Systematic Literature Review was employed to synthesize peer-reviewed studies published between 2020 and 2025. Data were collected from reputable academic databases and analyzed through thematic analysis and integrative synthesis to identify structural and adaptive dimensions of resilience. The findings reveal that risk management functions as the structural foundation of resilience through systematic risk identification, Enterprise Risk Management integration, and risk-based planning and budgeting. However, sustainable resilience requires complementary strategic adaptation mechanisms, including organizational agility, digital transformation, business model innovation, and institutional adaptation. The discussion demonstrates that resilience emerges from the interaction between anticipation capacity and adaptive transformation, reinforced by psychosocial and community resilience dimensions. In conclusion, organizational resilience in the era of global crises is achieved through systemic alignment between risk governance structures and adaptive strategic processes, enabling organizations to anticipate, cope, and transform in uncertain environments.